2011
DOI: 10.1002/app.34111
|View full text |Cite
|
Sign up to set email alerts
|

Polylactide toughening with epoxy‐functionalized grafted acrylonitrile–butadiene–styrene particles

Abstract: Glycidyl methacrylate functionalized acrylonitrile-butadiene-styrene (ABS-g-GMA) particles were prepared and used to toughen polylactide (PLA). The characteristic absorption at 1728 cm À1 of the Fourier transform infrared spectra indicated that glycidyl methacrylate (GMA) was grafted onto the polybutadiene phase of acrylonitrile-butadiene-styrene (ABS). Chemical reactions analysis indicated that compatibilization and crosslinking reactions took place simultaneously between the epoxy groups of ABS-g-GMA and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
79
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(85 citation statements)
references
References 52 publications
6
79
0
Order By: Relevance
“…This facilitated the pull-out of the copolymers generated from the interface to the PLA matrix, leading to the generation of more co-polymers in the interfacial regions and the finer distribution of the EGMA phase. In a work reported by Sun et al [32], ABS-grafted glycidyl methacrylate (ABS-g-GMA) was used as a toughening agent. They showed that the impact strength and elongation at a break of PLA could be improved by incorporating ABS-g-GM.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…This facilitated the pull-out of the copolymers generated from the interface to the PLA matrix, leading to the generation of more co-polymers in the interfacial regions and the finer distribution of the EGMA phase. In a work reported by Sun et al [32], ABS-grafted glycidyl methacrylate (ABS-g-GMA) was used as a toughening agent. They showed that the impact strength and elongation at a break of PLA could be improved by incorporating ABS-g-GM.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…Previous studies (Ihm and White, 1996;Heino et al, 1997;Papadopoulou and Kalfoglou, 2000;Pracella et al, 2002) to the effectiveness of compatibilizers can be found in literature, but quite often they compare (commercially available) compatibilizing agents with different grafting contents. As the grafting content is known to influence the degree of reaction (Sun et al, 2011) and thereby the compatibilization effect, it remains quite difficult to draw straightforward conclusions as to the actual effectiveness of the individual compatibilizer chains and their grafted functional groups. Within the current study, the grafting content is therefore explicitly the same for all compatibilizers.…”
Section: Introductionmentioning
confidence: 99%
“…Within the current study, the grafting content is therefore explicitly the same for all compatibilizers. Additionally, a low grafting content is taken to avoid agglomeration of the functional groups (Sun et al, 2011) and to maintain economic viability of the proposed solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Sun et al explored the use of glycidyl methacrylate functionalized acrylonitrile-butadiene-styrene (ABS-g-GMA) core-shell particles to toughen PBT. [39] This ABS-g-GMA copolymer contained reactive epoxy groups which could react with PBT end groups under melt conditions. Thus, the interfacial tension decreased between PBT and blends.…”
Section: Introductionmentioning
confidence: 99%